Modeling and Prioritizing Financing Methods for Different Economic Sectors in Iran Using a Multi-Criteria Decision-Making Approach (ANP-TOPSIS) - Alipour Rad, Hossein; Aghajani, Habib; Naqdi, Sajjad (Business, Marketing, and Finance Open, 2026)
This study aimed to develop a structured decision-making model to evaluate and prioritize financing methods for different economic sectors in Iran, with a particular focus on the National Iranian Gas Company (NIGC). This applied research used a descriptive-analytical design integrating the Analytic Network Process (ANP) and the TOPSIS techniques. Financial statements from 20 NIGC subsidiaries over five years were analyzed to identify key criteria influencing financing method selection, including bankruptcy risk, cost of financing, expected debt ratio, interest rate, and degree of corporate control. Data were collected from 20 financial experts using a researcher-developed questionnaire and semi-structured interviews. Expert judgments were aggregated using the geometric mean and analyzed through pairwise comparisons in the ANP framework. The TOPSIS technique was employed to model interrelations among criteria, and the ANP supermatrix was used to derive the final weights and rankings of criteria and financing alternatives. The results revealed that bankruptcy risk, cost of financing, and expected debt ratio were the most influential criteria shaping financing decisions, while tax advantage and earnings per share had minimal influence. Among financing options, inter-unit loans received the highest priority, followed by capital increases from the parent company, whereas bank loans ranked lowest. Validation analysis showed that applying the proposed model reduced the weighted average cost of capital (WACC) in 10 out of 13 subsidiaries, indicating its effectiveness in lowering financing costs and improving capital allocation efficiency. The proposed ANP-TOPSIS model offers a robust and structured framework for optimizing financing strategies, enabling organizations to minimize capital costs, enhance financial resilience, and reduce reliance on costly external borrowing.